Characteristics of Residents' House in Bukit Malintang Village, Sungai Aur Subdistrict, West Pasaman Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to determine the condition of the characteristics of the residents' houses in Bukit Malintang village, Sungai Aur Subistrict, West Pasaman Regency. This type of research is descriptive with survey methods and quantitative analysis with a total sample of 40 residential houses. Based on the research, it was found that 52.4% had a ceiling height of ≥ 2.4 m and 5% had a height of ≤ 2.4 m and all the ceilings of these residents' houses were easy to clean. Most of the residents' houses have a rough cement floor of 70%, some houses already use ceramics and granite with a percentage of 17.5%, 5% plank flooring, the condition of the floor is also easy to clean, for the condition of doors, windows and ventilation as much as 100% functioning properly and in good condition. Clean water sources from PAM are 60%, water sources from wells are 27.5% and there are several houses that have two sources of clean water as much as 12.5%. From one house to another, the number of family members varied greatly, the number of family members with more than 4 people was 70% and the number of family members with less than 4 people was 30%. The number of rooms in each house is of course also different where as much as 5% have 1 room, 52.5% have 2 rooms, 37.5% have 3 rooms and as much as 5% have 4 rooms but all of them do not have a minimum area of 8 m2. The average house area is 6 x 12 m2 , 6.5 x 12 m2 and 6.5 x 11 m2 . At home residents also already have a source of lighting / artificial lighting (electricity). Disposal of household waste, on average, already has a safe distance from the house so it doesn't smell and contaminate clean water. There are still a number of houses that do not have proper sanitation and still live in mosques or prayer rooms around their homes